Gravitational interactions of integrable models - Abdalla, E.; Abdalla, MCB (Elsevier B.V., 1996)
We couple non-linear sigma-models to Liouville gravity, showing that integrability properties of symmetric space models still hold for the matter sector. Using similar arguments for the fermionic counterpart, namely Gross-Neveu-type models, we verify that such conclusions must also hold for them, as recently suggested.